Theoretical insights and implications of bouncing cosmology in $$f(\mathcal {R},T^2)$$ f ( R , T 2 ) theory - M. Sharif; M. Zeeshan Gul; I. Hashim (European Physical Journal C: Particles and Fields)
Abstract In this paper, we explore cosmological bouncing solutions to investigate the cosmic evolution in the framework of energy-momentum squared gravity. We consider flat Friedmann–Robertson–Walker spacetime with a perfect matter distribution. We assume two different functional forms of $$f(\mathcal {R},T^2)$$ f ( R , T 2 ) gravity model to examine the impact of this modified framework in the evolution of the universe. Furthermore, we consider a specific scale factor to investigate different cosmological parameters, analyzing the evolutionary behavior of the universe in this gravity. We also perform stability analysis using the perturbation technique. Our findings indicate that the null energy condition violates at the bounce point and equation of state parameter exhibits characteristics of a quintessence era or phantom regimes. These aspects highlight the complex interplay between energy conditions and stability in bouncing cosmological model. We conclude that the $$f(\mathcal {R},T^2)$$ f ( R , T 2 ) theory successfully provides viable alternatives to the standard cosmological scenarios, offering insights into the early universe and the nature of gravity.